The effect of bound polyphenols on the fermentation and antioxidant properties of carrot dietary fiber in vivo and in vitro. Issue 1 (8th January 2020) - Liu, Shuai; Yu, Qiang; Huang, Hairong; Hou, Kunyou; Dong, Ruihong; Chen, Yi; Xie, Jianhua; Nie, Shaoping; Xie, Mingyong
Abstract : Growing attention has been paid to the importance of bound polyphenols in dietary fiber. Abstract : Growing attention has been paid to the importance of bound polyphenols in dietary fiber. This study aimed to elucidate the effect of bound polyphenols on the fermentation and antioxidant properties of carrot dietary fiber (CDF) in vivo and in vitro . Compared with CDF treatment, 16S rRNA pyrosequencing of in vivo mice feces and in vitro human fecal fermentation samples showed that dephenolized carrot dietary fiber (CDF-DF) treatment decreases operational taxonomic units (OTUs), ACE and Chao1 indexes, increases Firmicute / Bacteroidetes ratio and relative abundance (RA) of Parabacteroides at phylum, restrains RAs of typical beneficial bacteria as well as improves RAs of various harmful bacteria at genus. Meanwhile, short-chain fatty acid (SCFA) contents were lower, while the pH value was higher in the CDF-DF group than those in the CDF group. Interestingly, the combination of bound polyphenols and CDF-DF (CDDP) could recover these indexes influenced by the removal of bound polyphenols in in vitro fermentation samples. Furthermore, the CDF-DF-fed mice exhibited higher MDA content and lower SOD and GSH-Px activities in the colon. The cellular antioxidant activity (CAA) value of CDF-DF was lower than that of CDF and CDDP. These results revealed that bound polyphenols significantly contribute to the fermentation and antioxidant properties of CDF.